AISHa mechanical study and commissioning. Issue 11 (2nd December 2019) - Noto, Francesco; Costa, Giuseppe; Celona, Luigi; Chines, Francesco; Gammino, Santo; Leonardi, Ornella; Marletta, Salvatore; Torrisi, Giuseppe
ABSTRACT: The ion sources for accelerators devoted to medical applications must provide intense ion beams, with high reproducibility, stability and brightness. AISHa (Advanced Ion Source for Hadron therapy) is a compact ECRIS whose hybrid magnetic system consists of a permanent Halbach-type hexapole magnet and a set of independently energized superconducting coils. These coils will be enclosed in a compact cryostat with two cryocoolers for LHe-free operation. The AISHa ion source has been designed by taking into account the typical requirements of hospital-based facilities, where the minimization of the mean time between failures (MTBF) is a key point together with the maintenance operations which should be fast and easy. It is a multipurpose device, operating at 18 GHz, in order to achieve higher plasma densities able to provide enough versatility for future needs of the hadron therapy, including the ability to run at larger microwave power to produce different species and highly charged ion beams. In this paper, the innovative solutions, used for the plasma containment chamber and for the permanent magnet hexapole holder, are presented to solve the insulation and structural issues. The choice of the different materials used is hereinafter discussed together with all the involved processes (spinning, curing and machining). The glass fibers and carbon fibers are used to reinforce polymer matrices and give rise to structural composites and composites by molding. The paper shows also some results of ion source commissioning along with next developments. Innovative active coupling techniques are planned to be tested to optimize the first pass wave absorption, which plays an important role in the coupling optimization of the new-generation ECRIS.